Saberes e práticas de ensino de História em escolas rurais (um estudo no município de Araguari MG, Brasil) - Silva Júnior, Astrogildo Fernandes da (2007)
This work has as object of study the education, the knowledge and the pedagogical practices of History teachers in the basic education of rural schools in Araguari - MG, Brazil. The research specific objectives are: 1) to describe and interpret the scenery, the socio-economic and cultural aspects of Araguari - MG, and especially, the conditions in which the rural education is accomplished; 2) to understand the process of construction of the History teachers educational identity in the historical context of the rural education in Brazil and in Araguari-MG; 3) to analyze the constitution of knowledge and History teaching practices in the basic education of the rural schools in Araguari- MG. It is a qualitative research, whose methodological approach is inspired by the thematic oral history. Two administrative managers of the rural education and a group of seven History teachers of the town and state schools were interviewed. The teachers work for the elementary and high school levels. Oral narratives were transcribed and textualized with the objective of producing a reflection on the needs, difficulties and possibilities of pedagogic work in the area of History in the rural schools, regarding the process of construction of the educational identity, the school identity as well as the student's singularities of the school culture in the rural area. The oral sources were complemented by several written sources (laws, curricula, institutional guidelines, newspapers and textbooks), iconographic sources (pictures) and statistical data. The study revealed that the rural area of Araguari - MG is marked by permanencies and discontinuities inserted in the context of socioeconomic and cultural transformations, that characterize the Brazilian rural scenery in the last decades. There are several types of students in the investigated rural schools; there are differences of family income, geographical origin, gender, age, level of information and sociability; religion, etc. They come from producers, farmers or rural workers families. Many of them are migrants of other areas what constitute the so called new rural". The classrooms are multicultural spaces. The collaborating teachers were unanimous in affirming that the initial education didn't prepare the students for the rural reality. Therefore, they demand continuous education to assist the specificities of the school context, a right that, in spite of being prescribed by Law, it is not insured in practice. In their narratives, they evidenced the commitment with knowledge and History teaching practices that make sense for the student and deal with his reality. Regarding the meaning of the History teaching, there are different positions: some teachers are more worried about the student's education while facing the job market and adapting themselves to the rural reality. Others defend a more critical education, the student's autonomy and the construction the citizenship. We concluded that the school education for the people that live and work in the field should make possible the understanding and the amplification of the opportunities of the subjects so that they are capable to struggle for the necessary transformations in the socio, economic and cultural reality. In that sense, the academic researches in collaboration with the rural schools can be a way of changes of the educational process, as they value and evidence problems and possibilities.